Integrating Local Wisdom into Numeracy Literacy: An Analysis of Students’ Competence in the Number Domain in Sigi Regency, Indonesia - Hajerina, Hajerina; Napitupulu, Mery; Lefrida, Rita; Walanda, Richard Albert (FKIP Universitas Lampung, 2025)
Numeracy literacy is one of the basic competencies that support students' success in academic and social life. This study aims to analyze the numeracy literacy skills of junior high school students in Sigi Regency, Central Sulawesi Province, Indonesia, particularly in the domain of numbers, based on local wisdom such as the traditional Souraja buildings and agricultural practices of the residents of Sigi Regency. The sample comprised 120 eighth-grade students from six public junior high schools in Sigi Regency, representing diverse geographical characteristics (mountainous, rural, and urban) and varying educational performance levels. They were selected through purposive sampling and the mixed methods approach with an Explanatory Sequential Design as the research methodology. Data were collected using a numeracy literacy test developed using the AKM framework and numeracy competence indicators from the Ministry of Education, Culture, Research, and Technology (2023). The results showed that only 10% of pupils reached the